Response of Bone Metabolism Markers to Ice Swimming in Regular Practitioners - Mu, Shuai; Xia, Yang; Wu, Qijun; Ji, Chao; Dai, Huixu; Zhang, Ming; Jiao, Jiao; Shi, Feng; Liu, Shengye; Wang, Guangbin; Shen, Tao; Tian, Ye; et al. (Frontiers in Physiology, 2021)
Objective: Both exercise and cold exposure cause physiological stress and they often occur in combination. However, the effects of exercise during severe cold on variation in bone metabolism in humans have remained elusive. The aim of this study was to investigate the variations in circulating bone metabolism markers after ice swimming (IS). Methods: Eighty-seven women and men aged 42–84 years old were recruited to perform regular IS activities. Serum parathyroid hormone (PTH), total calcium (Ca2+), total phosphorus (Pi), total magnesium (Mg2+), N-terminal osteocalcin (N-MID), total propeptide of procollagen 1 (TPINP), and C-terminal telopeptide of type 1 collagen (β-CTX) were measured 30 min before and 30 min after IS. Bone mineral content (BMC) and bone mineral density (BMD) were assessed at lumbar spine 1–4 (L1–L4) and femoral neck (FN). The IS habits were obtained from questionnaires and the 10-year probability of osteoporotic fracture was calculated using the FRAX® tool with and without a BMD value of the FN. Results: There were significant increases in PTH (median, 40.120 to 51.540 pg/mL), Ca2+ (median, 2.330 to 2.400 mmol/L), and Pi (median, 1.100 to 1.340 mmol/L) and significant decreases in TPINP (median, 38.190 to 36.610 ng/mL) and β-CTX (median, 0.185 to 0.171 ng/mL), while there was a trend for increased serum Mg2+ (P = 0.058) but no significant change in N-MID (P = 0.933) after IS in all subjects. The increases in the proportions of cases of hyperparathyroidemia, hypercalcemia and hyperphosphatemia in those performing IS were statistically significant. The baseline levels and the changes of bone metabolism markers had associations with osteoporosis and bone status, but these may be age and sex dependent. Finally, there were significant correlations among the bone metabolism markers. Conclusion: IS caused significant alterations in bone metabolic markers, specifically, increases in PTH, Ca2+ and Pi should raise concerns about potential cardiovascular health risks in severe cold exercise. Additionally, a divergence between PTH elevation and a decline in bone turnover, which shown a special change of bone metabolism after IS and may suggest potential therapeutic implications of cold exercise in PTH and bone metabolic disorders.